Plato on Women’s Natural Ability: Revisiting Republic V and Timaeus 41e3–44d2 and 86b1–92c3 - Harry, Chelsea; Ron, Polansky (Apeiron, 2016)
Abstract Despite the prominent argument for equal educational opportunity for women in Republic V, commentators frequently question Plato’s sincerity, the quality of the case made, or its significance. Undermining confidence in Plato’s advocacy of female equality are derogatory remarks about women in this and other dialogues. Since we take Plato to be sincere in the argument in Republic V, we reconcile his conclusions there about the equal educational opportunity for women with these seemingly problematic remarks by suggesting that the remarks reflect the interlocutors involved in the dialogue and conventional Athenian prejudices of that time rather than ideas that Plato held to be true. We take seriously the observation of Levin 1996, 14, “in none of those passages in which Plato makes derogatory remarks about women does he use phusis to explain why they behave in the ways of which he is critical.” Hence Plato never suggested that women were by nature limited to the position they occupied socially and politically in 5th or 4th century Athens; he understood the difference between the way they were by convention and the way that they could be, in accordance with their nature, were they to develop their natural capacities through education. We examine carefully Plato’s argument for the equal nature of women in Republic V to defend its viability. The provocation is our not finding in the extensive secondary literature a really detailed treatment of the actual argument and appreciation that it is intended as a sound philosophical argument. We then turn to the devolution schemes in Timaeus 41e–44d and 86b–92c, which again touch on the nature of women and appear to counter the position we attribute to Plato, to show that they are really supportive of our account. Both the Republic and Timaeus limit the natural differences between males and females to body-type. Therefore, even relative physical weakness of women’s bodies does not much problematize for Plato that their natural abilities are equal to those of men, where nature in these contexts means suitability to perform certain functions.
Keywords: dept.phi

Psychoanalysis and Repetition: Why Do We Keep Making the Same Mistakes? - Nasio, Juan-David (SUNY series in contemporary French thought, 2019)
In Psychoanalysis and Repetition, Juan-David Nasio, one of the leading contemporary Lacanian psychoanalysts in France, argues that unconcious repetition represents the core of psychoanalysis as well as no less than the fundamental constitution of the human being--back cover.
Keywords: Lacan, Jacques, 1901-1981; Psychoanalysis; Repetition (Philosophy); dept.phi; faculty_collection

Chronos in Aristotle's Physics: On the Nature of Time - Harry, Chelsea C. (SpringerBriefs in philosophy, 2015)
Keywords: Aristotle. Physics; Time; Philosophy; Philosophy of nature; Philosophy; Physics; dept.phi; faculty_collection

Sabbatical leave report: sabbatical Fall 2013 - Volkman, Richard (2013)
This sabbatical leave was devoted to revising and editing material for a book project with the working title, Meditations on Heroic Individualism. The principle objective was to have a finished manuscript, ready for submission to publishers. Additionally, a proposal was developed to add Special Topics course, Ethical Individualism, as a permanent course.
Keywords: dept.phi; faculty_collection; sabbatical_report

The "Backwards, Forwards and Sideways" Changes of Ict: Ethicomp 2010: Proceedings of the Eleventh International Conference - International Conference on the Social and Ethical Impacts of Information and Communication Technologies (11th : Universitat Rovira i Virgili, Tarragona; Arias-Olive, Mario; Bynum, Terrell Ward; Rogerson, Simon; Torres-Coronas, Teresa; Centre for Computing and Social Responsibility (Universitat Rovira i Virgili, 2010)
"The purpose of this series is to provide an inclusive European forum for discussing the ethical and social issues associated with the development and application of Information and Communication Technology (ICT). The conferences are held every 18 months."--Introduction.
Keywords: Congresses; Congresses; Information technology; Information technology; Moral and ethical aspects; Professional ethics; dept.phi; faculty_collection

Oedipus: The Most Crucial Concept in Psychoanalysis - Nasio, Juan-David (SUNY series in contemporary French thought, 2010)
In this work, the author argues that the Oedipus complex represents the core of psychoanalysis as well as the fundamental constitution of the human being.--(Source of description unspecified.)
Keywords: Oedipus complex; Psychoanalysis; Oedipus Complex; Psychoanalytic Therapy; dept.phi; faculty_collection

Reimagining a Lost Armenian Home: The Dildilian Photography Collection - Marsoobian, Armen (I.B. Tauris, 2017)
For nearly a century members of the Dildilian family practiced the art of photography in Ottoman Turkey, Greece and the United States. This book contains over 200 photographs, primarily from the Ottoman era, beginning with the creation of the family business by Tsolag Dildilian in Sivas in central Turkey in 1882 and concluding in 1922 in Samsun, when the family was forced into exile in Greece. The photographs and the stories that unfold around them capture a defining period in the nearly three thousand year history of the Armenians in Anatolia and the Armenian Highlands. The early-twentieth century witnessed the violent erasure of the Armenians from their historic homeland, with catastrophic effects for the Dildilian family and their community. Yet this was also a period of unprecedented educational, cultural and commercial development for the Armenians. The Dildilian family was intimately involved in the triumphs and tragedies of these years and this book, through its rich pictorial history, sheds unprecedented light on the real-life experiences of Armenians in the devastating years of the Armenian Genocide and beyond. It is an unusual and original contribution to the social history of the Near East.
Keywords: Dildilian family; Armenians; Pictorial works; Portraits; Armenia; dept.phi; faculty_collection

Heidegger in France - Janicaud, Dominique (Studies in Continental thought, 2015)
Dominique Janicaud claimed that every French intellectual movement--from existentialism to psychoanalysis--was influenced by Martin Heidegger. This translation of Janicaud's landmark work, Heidegger en France, details Heidegger's reception in philosophy and other humanistic and social science disciplines. Interviews with key French thinkers such as Françoise Dastur, Jacques Derrida, Éliane Escoubas, Jean Greisch, Philippe Lacoue-Labarthe, Jean-Luc Marion, and Jean-Luc Nancy are included and provide further reflection on Heidegger's relationship to French philosophy. An intellectual undertaking of authoritative scope, this work furnishes a thorough history of the French reception of Heidegger's thought.--Publisher website.
Keywords: 20th century; Philosophers; France; Heidegger, Martin, 1889-1976; Philosophy, French; Interviews; dept.phi; faculty_collection

Fragments of a Lost Homeland: Remembering Armenia - Marsoobian, Armen (I.B. Tauris & Co. Ltd., 2015)
Keywords: 1801-1900; Dildilian family; Armenian Genocide, 1915-1923; History; Personal narratives, Armenian; Armenian Genocide, 1915-1923; Armenia; SCSU Faculty Scholar Award; award_winner; dept.phi; faculty_collection

Pornography As Simulation - Bach, T. (Porn - Philosophy for Everyone, 2010)
Keywords: Folk-psychological prowess, on MTV's The Hills; Mental simulation, and the "off-line" heuristic; Modern perversion of mental simulation; Money, lesbians and woodsmen; Philosophers and psychologists, "theory-theory" approach to folk psychology; Pornography as simulation; Simulating a day at the office; Tools of folk psychology-human beings, are prolific psychologists; World of actual sexual relationships-dangerous sexually transmitted diseases, more lethal than ever; dept.phi; origin of simulation-pornographic appropriation of mind-reading skill, and mentalizing ability

Foreword - Bynum, T.W. (Ethical Issues and Social Dilemmas in Knowledge Management: Organizational Innovation, 2010)
Keywords: dept.phi

Jokers on the mountain: In defense of gratuitous risk - Lockwood, H.H. (Climbing - Philos. for Everyone: Because It's There, 2010)
Keywords: "Jokers on the Mountain"; "The Outside Prognosticator: Really Quite Stupid"; Dan Osman's new game of controlled falling as a "Stupid Pastime"; Maria Coffey's book, Where the Mountain Casts Its Shadow; Mountaineering: The Freedom of the Hills; The Rule of Rescue; The predecessor of the so-called "Beacon Bill"; dept.phi

Federative Global Democracy - Cavallero, E. (Global Democracy and Exclusion, 2011)
Keywords: Allocation of sovereign competences - over territorial jurisdictions; Exercise of sovereign competences, at every level - constrained by effective global human rights regime; Federative global democracy; Global Federative Model and State sovereignty - internal and external aspects; Global federative model and its aims - avoiding concentration of sovereign powers in territorial jurisdiction; Gould, defending second principle of political inclusion - ground rights of participation; Internal sovereignty, exclusive, irrevocable legal competence - making policy to govern; Internalization condition, external costs internalized - through constitution of composite polities; Local democratic institutions - and global ones; Polity's legal competence, sovereign - exclusive and irrevocable for territory; dept.phi

Do Differences in Grammatical Form between Languages Explain Differences in Ontology between Different Philosophical Traditions?: A Critique of the Mass-Noun Hypothesis - Yang, X. (Dao, 2011)
It is an assumed view in Chinese philosophy that the grammatical differences between English or Indo-European languages and classical Chinese explain some of the differences between the Western and Chinese philosophical discourses. Although some philosophers have expressed doubts about the general link between classical Chinese philosophy and syntactic form of classical Chinese, I discuss a specific hypothesis, i. e., the mass-noun hypothesis, in this essay. The mass-noun hypothesis assumes that a linguistic distinction such as between the singular terms and the predicates is sufficient to justify or necessarily leads to a specific ontological distinction such as the distinction between the particular and the universal. I argue that one cannot read off semantic properties simply from syntactic ones and hence the syntactic differences do not automatically translate into the semantic differences between languages, that the syntactic features of Chinese nouns do not have explanatory significance in explaining why the particular-universal problem does not arise in the classical period of Chinese philosophy, and that the part-whole ontology allegedly informed by the mass-noun-like semantics does not provide a natural or intuitive picture of the language-world relation. © Springer Science+Business Media B.V.2011.
Keywords: Mass noun and count noun; Ontology; Syntactic and semantic distinction; dept.phi; peer-reviewed

Two self-critiques in Heidegger's critique of metaphysics - Gilliland, R. (Journal of Speculative Philosophy, 2012)
This article traces shifts in Heidegger's stance toward metaphysics after fundamental ontology and argues that these shifts reflect changes in his conceptions of ontological difference and temporality that pave the way for his mature thought. Copyright © 2012 The Pennsylvania State University.
Keywords: dept.phi; ⚠️ Invalid DOI

A psychoanalyst on the couch - Nasio, J.-D.; Raffoul, F.; Pettigrew, D. (A Psychoanalyst on the Couch, 2012)
An interview with Juan-David Nasio. In A Psychoanalyst on the Couch, we find the noted psychoanalyst and Lacan commentator Juan-David Nasio on the analyst's couch himself. In the interview that makes up this book, he provides insight into his forty-year career as a writer and practitioner, elaborating on Freudian and Lacanian concepts important to his work and reflecting on broad issues related to psychology and culture-as well as personal remembrances. The result is an intimate and wide-ranging look at the man and thinker, both an introduction to his work and a deeper look at his approach and outlook. © 2012 State University of New York. All rights reserved.
Keywords: dept.phi

The task of justice - Pettigrew, D. (Jean-Luc Nancy and Plural Thinking: Expositions of World, Ontology, Politics, and Sense, 2012)
Keywords: dept.phi

Roman Catholic monasticism in Poland: A brief overview of selected issues - Górniak-Kocikowska, K. (Monasticism in Eastern Europe and the Former Soviet Republics, 2015)
Keywords: dept.phi

In defense of the critical philosophy: On Schelling's departure from Kant and Fichte in Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (1796/1797) - Harry, C.C. (Journal of Speculative Philosophy, 2015)
This article considers the second treatise of Schelling's Abhandlungen zur Erläuterung des Idealismus der Wissenschaftslehre (Treatises Explaining the Idealism of the Science of Knowledge, 1796/97), a lesser-known work from the early Schelling. Here, Schelling proposes to defend the critical position insofar as it purports to be a system based on human reason, but instead he issues a backhanded critique of the assumption on behalf of the critical philosophers to try and limit the bounds of pure reason by means of their own use of reason. Schelling then offers an alternative way to think about the relationship of mind (Geist) and matter in nature. This article argues that Schelling's actual explanation of the critical philosophy as a position founded by reasonable minds ultimately belies his promise to defend it, thus calling into question that Schelling's thought prior to 1800 was a mere reiteration of Kantian/Fichtean transcendentalism. Copyright © 2015 The Pennsylvania State University, University Park, PA.
Keywords: Critical philosophy; Fichte; Kant; Naturphilosophie; Shelling; dept.phi

On the fundamental dissimilarity of aristotelian and Kantian time concepts - Harry, C.C. (Idealistic Studies, 2015)
In Aristotle's Physics iv 10-14, Aristotle argues for a time concept derived with, on a weak version, sense perception, and, on a strong version, from sense perception along with intellection (nous), from change in nature. On both accounts, actualized time for Aristotle requires cognitive faculties. Aristotle's time concept has thus been linked with Kant's treatment of time in the Transcendental Aesthetic of his First Critique. More importantly, the conclusion that time is "unreal" for Aristotle elicits charges of adulterating Aristotle's conclusions by reading Aristotle's Physics with a Kantian lens. In this paper, I examine the context of Kant's conclusions about time and, by way of a contrast between the Aristotelian and Kantian projects, argue for a fundamental dissimilarity of their accounts. And yet, I reserve the possibility that one both ascent to this fundamental dissimilarity and hold that Aristotle was not a temporal realist. © 2015. Idealistic Studies.
Keywords: dept.phi; peer-reviewed

Taking Time - Harry, C.C. (SpringerBrief. Philos., 2015)
Despite the language we saw in the previous chapter, which allowed for time apprehension by perception and marking, in Physics iv 14, Aristotle famously argues that time is dependent on nous. © 2015, The Author(s).
Keywords: Human Child; Nonhuman Animal; Pure Actuality; Sense Perception; Time Perception; dept.phi

The Armenian Genocide of 1915: Armen T. Marsoobian explores the complex history of one of the 20th-century's worst and most neglected crimes against humanity - Marsoobian, A.T. (History Today, 2015)
Keywords: dept.phi; ⛔ No DOI found

The task of justice - Pettigrew, D. (Pathways to Reconciliation: Between Theory and Practice, 2016)
Contemporary discourse about human rights makes pragmatic use of the 1948 United Nations Universal Declaration on Human Rights, as the Declaration presents a set of guidelines that are based on assumptions about the nature of human beings: Their thoughts, ideas, freedom of expression and freedom of association.1 Article 1 of the Declaration states, for example, that ‘All human beings are born free and equal in dignity and rights. They are endowed with reason and conscience and should act towards one another in a spirit of brotherhood.’ The document engages the idea of the human being as having rights, regardless of ethnicity or gender. Such rights include life, protection from harm, and access to the latest in scientific technology.2 © Philipa Rothfield, Cleo Fleming and Paul A. Komesaroff 2008.
Keywords: dept.phi

Virtues, vices, and situations: What warrants the ascription of character traits - Yang, X. (Journal of Theoretical and Philosophical Psychology, 2016)
In recent years, situationism in psychology has caught the attention of philosophers. Some have defended it. Some have argued against it. The situationist has challenged the traditional view shared by personality psychology and virtue ethics that people differ in terms of character or character traits and that we can explain and predict people's behavior by character traits people have. Previous responses to situationism try to show that experiments from social psychology do not undermine the traditional view. I agree and will further argue that the fact that experiments do not undermine the traditional view is not sufficient to warrant the attribution of character traits, and that some philosophical arguments are needed given that not enough empirical data that show a high degree of behavioral consistencies are available. I first offer an account of the ordinary attribution of character traits according to which having character traits is a matter of degree, and argue that the ordinary attribution account comes from the Aristotelian moral psychology and is consistent with a long-standing tradition, the trait paradigm, in personality psychology. Second, I argue that although situational factors play some role in explaining and predicting behavior, the attribution of character traits plays a primary and indispensable role. Third, I argue that ordinary attribution of character traits has important functions in our moral life, which cannot be fulfilled by the attribution of local traits suggested by the situationist. I also argue that the ethical management of situations recommended by the situationist can help in getting things right, but is not sufficient to be the adequate foundation for our normative discourse. © 2016 American Psychological Association.
Keywords: Attribution of character traits; Crosssituational consistency and variation; Local traits; Situationism; Virtues; dept.phi

The computer revolution and the problem of global ethics - Gorniak-Kocikowska, K. (Computer Ethics, 2017)
The author agrees with James Moor that computer technology, because it is 'logically malleable', is bringing about a genuine social revolution. Moor compares the computer reVolution to the 'industrial revolution' of the late 18th and the 19th centuries; but it is argued here that a better comparison is with the 'printing press revolution' that occurred two centuries before that. Just as the major ethical theories of Bentham and Kant were developed in response to the printing press revolution, so a new ethical theory is likely to emerge from computer ethics in response to the computer revolution. The newly emerging field of information ethics, therefore, is much more important than even its founders and advocates believe. © John Weckert 2007. All rights reserved.
Keywords: Computer ethics; Computer revolution; Global ethics; Industrial revolution; Printing revolution; Professional ethics; dept.phi

Editors' Introduction - Lindert, J.; Marsoobian, A.T. (Multidiscipl. Perspect. on Genocide and Memory, 2018)
Keywords: dept.phi

The Armenian genocide in film: overcoming denial and loss - Marsoobian, Armen T (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi

Cinematic witnessing of the genocide in Bosnia 1992–1995: toward a poetics of responsibility - Pettigrew, David (The history of genocide in cinema: atrocities on screen, 2017)
Keywords: dept.phi

False friends and false coinage: a tool for navigating the ethics of sociable robots - Elder, Alexis (ACM Sigcas Computers and Society, 2016)
Keywords: dept.phi

The Factor of Listening in Karl Jaspers’ Philosophy of Communication - Górniak-Kocikowska, Krystyna (Philosophical Faith and the Future of Humanity, 2012)
Jaspers’ views on communication and his approach to the question of listening, both underwent an evolution in which World War II and the first years thereafter played a crucial role. In this process, Jaspers journeyed from listening to the great minds of the past, through an inward dialogue with them, to one-sided lecturing while his audience was engaged in a straight-line listening, to an intimate dialogue with those he considered like-minded, to a multi-faceted dialogue, and finally to listening to his contemporaries and learning how to practice transactional listening-in-conversation in the process of a multi-layered communication he called a loving struggle. This evolution, paralleled by the transition of Japers’ philosophy from local-centered to world-centered makes his thinking attractive and useful today.
Keywords: German Student; Great Mind; Nazi Regime; Political Involvement; Verbal Communication; dept.phi

Knowledge management and democracy: A critical review of some moral issues and social dilemmas - Gorniak-Kocikowska, K (Organizational Learning and Knowledge: Concepts, Methodologies, Tools and Applications, 2011)
The main problem discussed in this chapter is the question of compatibility between knowledge management in the knowledge economy and democracy in the ICT-driven global society. The assumption is made that democracy is the dominant form of organizing the global society on a variety of levels; and that it is regarded as desirable and morally superior in comparison with other such forms. © 2011, IGI Global.
Keywords: dept.phi

The eclipse and rebirth of american philosophical pluralism: a history lesson about his-tory - Marsoobian, Armen T (Wisdom, 2016)
Keywords: dept.phi

The path dependence of dynamic traditions and the illusion of cultural AIDS - Volkman, Richard (ACM Sigcas Computers and Society, 2016)
Keywords: dept.phi

Computer ethics beyond mere compliance - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2015)
Purpose – The paper aims to examine the nature of computer ethics as a field of study in light of 20 years of Ethicomp, arguing that computer ethics beyond mere compliance will have to be pluralistic and sensitive to the starting places of various audiences. Design/methodology/approach – The essay offers a philosophical rather than empirical analysis, but the ideal of open inquiry is observed to be manifest in the practice of Ethicomp. Findings – If computer ethics is to constitute a real engagement with industry and society that cultivates a genuine sensitivity to ethical concerns in the creation, development and implementation of technologies, a genuine sensitivity that stands in marked contrast to ethics as “mere compliance”, then computer ethics will have to persist in issuing an open invitation to inquiry. Originality/value – The celebration of 20 years of Ethicomp is an occasion to reflect on who we are and what we mean to be doing. Inclusive of previous accounts (e.g. Moor and Gotterbarn), while going beyond them, an inquiry-based conception of computer ethics makes room for all the various dimensions of computer ethics. ©Emerald Group Publishing Limited
Keywords: Collaboration; Community evolution; Computer ethics; Information ethics; Philosophy; Teaching innovations; dept.phi; peer-reviewed

Physics iv 10-11 as a Parallel Account - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
Given the context of the Physics just explored, it will not be a surprise if time (chrόnos) in Aristotle’s analytic of time turns out to be not a being qua itself but an attribute of motion, an interval.
Keywords: Infinite Divisibility; Infinite Time; Internal Inconsistency; Natural Object; Underlying Unity; dept.phi

Time in Context - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
The key to taking in Aristotle’s treatise on time is to approach it with the understanding that Aristotle was not a philosopher concerned with time —in questions about time or in delimiting the being of time.
Keywords: Accidental Change; Accidental Form; Natural Object; Predicative Change; Privative Form; dept.phi

Excellent online friendships: an Aristotelian defense of social media - Elder, Alexis (Ethics and Information Technology, 2014)
I defend social media's potential to support Aristotelian virtue friendship against a variety of objections. I begin with Aristotle's claim that the foundation of the best friendships is a shared life. Friends share the distinctively human and valuable components of their lives, especially reasoning together by sharing conversation and thoughts, and communal engagement in valued activities. Although some have charged that shared living is not possible between friends who interact through digital social media, I argue that social media preserves the relevantly human and valuable portions of life, especially reasoning, play, and exchange of ideas. I then consider several criticisms of social media's potential to host friendships, and refute or weaken the force of these objections, using this conception of a distinctively human shared life. I conclude that we should use the shared life to evaluate features of social media and norms for users' conduct.
Keywords: Aristotle; Data privacy; Friendship; Information technology; Privacy; Shared activity; Social media; Social networking (online); Social sciences; Valuable component; dept.phi

On the possibility of quantum informational structural realism - Bynum, Terrell Ward (Minds and Machines, 2014)
In The Philosophy of Information, Luciano Floridi presents an ontological theory of Being qua Being, which he calls "Informational Structural Realism", a theory which applies, he says, to every possible world. He identifies primordial information ("dedomena") as the foundation of any structure in any possible world. The present essay examines Floridi's defense of that theory, as well as his refutation of "Digital Ontology" (which some people might confuse with his own). Then, using Floridi's ontology as a starting point, the present essay adds quantum features to dedomena, yielding an ontological theory for our own universe, Quantum Informational Structural Realism, which provides a metaphysical interpretation of key quantum phenomena, and diminishes the "weirdness" or "spookiness" of quantum mechanics. © 2013 The Author(s).
Keywords: Dedomena; Digital ontology; Primordial qubit; Quantum information; Structural realism; dept.phi

Association and asylum - Cavallero, Eric (Philosophical Studies, 2014)
Keywords: dept.phi

Zhuangzi on friendship and death - Elder, Alexis (Southern Journal of Philosophy, 2014)
Zhuangzi suggests that death is a transformation that we commonly and mistakenly think means the end of someone but really just marks a new phase of existence. This metaphysical thesis is presented at several points in the text as an explanation of distinctively Daoist responses to death and loss. Some (such as Wong 2006) take a Daoist response to death, as presented by Zhuangzi, to indicate dual perspectives on friendship and death. But I argue that the metaphysical view sketched above is consistent with a unified perspective, allowing the Daoist to enjoy deep friendships without risking some potential for grief typically associated with strong attachment. However, it leaves the Daoist best suited to friendships with those who endorse the same metaphysics. Furthermore, while the grief associated with the death of a friend is somewhat mitigated, the Daoist has reason to mourn even given this thesis. © 2014 The University of Memphis.
Keywords: dept.phi

Situating the early schelling in the later positive philosophy - Harry, Chelsea C (Comparative and Continental Philosophy, 2014)
This is a translation of the second chapter of F.W.J. Schelling's Abhandlungen zur Erlaüterung des Idealismus der Wissenschaftslehre (1796-1797). It is preceded by a brief introduction in which I situate the chapter within Schelling's oeuvre and suggest that it is not only an early articulation of Schellingian Naturphilosophie, but also prescient, anticipating Schelling's later positive philosophy. © W. S. Maney & Son Ltd 2014.
Keywords: Naturphilosophie; Negative philosophy; Positive philosophy; Schelling; dept.phi

Helping students to see for themselves that ethics matters - Jagger, Suzy; Volkman, Richard (The International Journal of Management Education, 2014)
Business ethics education is experiencing a renaissance as recurring corporate scandals and malpractice over the last decade have ensured that most universities now see the subject as an important and necessary component of any business degree course. As well as integrating professional ethics into their curriculum, Business Schools are also developing standalone ethics courses, showing that they take seriously their responsibility to help prepare the next generation of managers to improve business' track record of transparency, accountability and sustainable development. However what are the learning approaches that will help to bring about real improvements in business ethics learning at university? This paper argues that a holistic approach to ethics teaching is needed, in which students are encouraged to develop ethical knowledge and skills within their personal value systems. In this way ethics does not become something apart but integrated into one's terms of reference. The paper discusses a particular pedagogic approach designed to develop a student's 'critical consciousness' using a student-led learning method in which students actively engage with important concepts and discuss the issues amongst themselves within an environment where they can speak freely. Qualitative interviews with a selection of undergraduates on the compulsory first year professional ethics module provide insight into the impact of the method on attitudes and behaviours. © 2013 Elsevier Ltd.
Keywords: Business ethics; Moral sensitivity; Teaching business ethics; Transformational learning; Values and integrity; Virtue ethics; dept.phi

The making of modern Turkey: nation and state in eastern Anatolia, 1913–1950 - Marsoobian, Armen T (Journal of Genocide Research, 2013)
Keywords: dept.phi

Collective intelligence and ethical individualism - Volkman, Richard (ACM Sigcas Computers and Society, 2013)
Keywords: dept.phi

Creating the Journal Metaphilosophy - Bynum, Terrell Ward (Metaphilosophy, 2011)
This brief article describes the circumstances that led to the creation of the journal Metaphilosophy in autumn 1968. A year after I had left graduate school, an unfortunate accident left me flat on my back for several weeks with nothing to do while recuperating from eye surgery. Bored, I decided to do something constructive, so I created a scholarly journal devoted to articles about the nature of philosophy, or how the different schools or branches of philosophy relate to each other, or how philosophy relates to other disciplines. I made up the word "metaphilosophy" to describe such content, and I decided to call the journal by that name. With help from my wife, from my best friend, and from my undergraduate philosophy mentor, the journal Metaphilosophy was launched. © 2011 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: dept.phi; editorial board; metaphilosophy; scholarly journal

Health, luck and moral fallacies of the second best - Cavallero, Eric (The Journal of Ethics, 2011)
Individuals who become ill as a result of personal lifestyle choices often shift the monetary costs of their healthcare needs to the taxpaying public or to fellow members of a private insurance pool. Some argue that policies permitting such cost shifting are unfair. Arguments for this view may seem to draw support from luck egalitarian accounts of distributive justice. This essay argues that the luck egalitarian framework provides no such support. To allocate healthcare costs on the basis of personal responsibility would arbitrarily and publicly burden socially detectable risk-takers while undetectable risk-takers continue to get a free ride. That problem is unavoidable even on the assumption that distributive institutions outside the healthcare sector are fully just. In actual, farfrom-just societies, imposing personal liability for the costs of voluntary risk taking would be wrong for an additional reason. Doing so would tend to magnify existing distributive injustices. These conclusions draw attention to two common 'moral fallacies of the second best' that can arise when applying ideal normative theory to matters of institutional design and in real-world policy contexts. © 2011 Springer Science+Business Media B.V.
Keywords: Egalitarianism; Health; Healthcare; Luck; Luck egalitaianism; Personal responsibility; Responsibility; dept.phi; peer-reviewed

Coercion, inequality and the international property regime - Cavallero, Eric (Journal of Political Philosophy, 2010)
Keywords: dept.phi

Philosophy in the Information Age - Bynum, Terrell Ward (Metaphilosophy, 2010)
Abstract: In the past, major scientific and technological revolutions, like the Copernican Revolution and the Industrial Revolution, have had profound effects, not only upon society in general, but also upon Philosophy. Today's Information Revolution is no exception. Already it has had significant impacts upon our understanding of human nature, the nature of society, even the nature of the universe. Given these developments, this essay considers some of the philosophical contributions of two “philosophers of the Information Age”—Norbert Wiener and Luciano Floridi—with regard to the nature of the universe, human nature, the nature of society, and the nature of “artificial agents” such as robots, softbots, and cyborgs.
Keywords: Artificial agents; Cybernetics; Cyborgs; Digital physics; Entropy; Inforg; Information; Information Age; Information Revolution; Information age; Information revolution; Infosphere; Luciano Floridi; Norbert Wiener; Qubits; Robots; Second law of thermodynamics; artificial agents; cybernetics; cyborgs; dept.phi; digital physics; entropy; inforg; information; infosphere; qubits; robots; second law of thermodynamics

Commodification and privacy: a Lockean perspective. - Volkman, Richard (HEC forum : an interdisciplinary journal on hospitals' ethical and legal issues, 2010)
This paper defends the thesis that privacy as a right is derived from fundamental rights to life, liberty, and property and does not permit restricting the commodification of bodily material; however, privacy as life, liberty, property does require conventions that ensure a robust and just market in bodily material. The analysis proceeds by defending a general commitment to liberty and markets, but not in the manner one might expect from a 'doctrinaire' libertarian. Ethical concerns about commodification are legitimate in the context of new medical and information technologies, but these concerns are not sufficiently well defined to justify political conclusions, since not every ethical concern is in itself a political concern, and the best way to resolve certain ethical difficulties is to draw up political boundaries that facilitate the discovery and testing of various solutions to our ethical puzzles. To illustrate the point, I will indicate how privacy as life, liberty, property defines such a dynamic solution to the problems of commodification of human bodily material and slippery information in insurance markets.
Keywords: *Ownership; *Privacy; Civil Rights; Commerce; Commodification; Human Body; Humans; John Locke; Liberalism; Markets; Natural rights; Ownership; Politics; Privacy; art; article; civil rights; commercial phenomena; dept.phi; human; organization and management; politics; privacy

Why information ethics must begin with virtue ethics - Volkman, Richard (Metaphilosophy, 2010)
The information ethics (IE) of Floridi and Sanders is evaluated here in the light of an alternative in virtue ethics that is antifoundationalist, particularist, and relativist in contrast to Floridi's foundationalist, impartialist, and universalist commitments. Drawing from disparate traditional sources like Aristotle, Nietzsche, and Emerson, as well as contemporary advocates of virtue ethics like Nussbaum, Foot, and Williams, the essay shows that the central contentions of IE, including especially the principle of ontological equality, must either express commitments grounded in the particular perspectives we already inhabit, or be without rational or ethical force for us. © 2010 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: Ethical individualism; Foundationalism; Information ethics; Particularism; Virtue ethics; dept.phi

The genocidal legacy of Radovan Karadžić - Pettigrew, David (Etnické komunity: hrdinové, šibalové a antagonisté Balkánu, 2017)
Keywords: dept.phi

Opportunity and responsibility for health - Cavallero, Eric (The Journal of Ethics, 2019)
Wealth and income are highly predictive of health and longevity. Egalitarians who maintain that this “socioeconomic-status gradient” in health is unjust are challenged by the fact that a significant component of it is owed to the higher prevalence of certain kinds of voluntary risk-taking among members of lower socioeconomic groups. Some egalitarians have argued that these apparently free personal choices are not genuinely free, and that those who make them should not be held morally responsible for the resulting harms to their health. I argue to the contrary that such choices usually are fully free, and that those who make them are responsible for their consequences. This does not imply, however, that society cannot also be responsible for those consequences. It is responsible for them if they are statistically foreseeable and avoidable outcomes of unjust public institutions and policies. I show that many of the harms to health that contribute to the voluntary behavioral component of the SES health gradient satisfy that description. Society can therefore be morally responsible for those harms, even though the individuals who suffer them are also fully responsible for them.
Keywords: Equality of opportunity; Health; Personal responsibility; SES gradient in health; Social responsibility; dept.phi; peer-reviewed

How do we make sense of the thesis “bai (white) ma (horse) fei (is not) ma (horse)”? - Yang, Xiaomei (Dao, 2019)
In this article, I introduce a new interpretation of the puzzling thesis “bai 白 (white) ma 馬 (horse) fei 非 (is not) ma 馬 (horse)” argued by Gongsun Long 公孫龍 in his essay “On White Horse (Bai Ma Lun 白馬論).” I argue that previous interpretations, which can be grouped under the name of “attribute-object interpretations,” are not satisfactory, and that the thesis on the new interpretation is not about attributes or objects, but about names. My argument focuses on the disagreement over inseparability of white (shou bai zhi zheng 守白之爭) between Gongsun Long and his interlocutor in the text of “On White Horse.” On my interpretation or the name interpretation, the disagreement is about whether constituents of a syntactically complex or multi-term name are separable or have their contextually independent meanings. Gongsun Long’s thesis makes perfect sense on my interpretation, and is supported by the text and other preserved texts collected in GongsunLong Zi 公孫龍子. The name interpretation can also make sense of some puzzling expressions of sophists in the classic period.
Keywords: Complex name; Descriptive phrase; Inseparability of white; Simple name; White Horse; dept.phi; peer-reviewed

Exchanging IRL for VR: experience machines and opportunity costs - Volkman, Richard (ACM SIGCAS Computers and Society, 2018)
Virtual Reality (VR) experiences have arrived for a wide audience, and some worry that VR experience entices us to abandon experience In Real Life (IRL). While such worries cannot be dismissed out of hand, they are liable to be imprecise and distorted without careful analysis of the opportunity costs of VR experience. Generally, we are not liable to abandon real experience for its virtual analogue. Even a perfect VR experience is generally not a perfect substitute for a like experience IRL. Instead, the success of VR will depend on its ability to produce experiences valued for what they actually are.
Keywords: dept.phi; experience machine; value theory; virtual reality

Criticism and compassion: the ethics and politics of Claudia Card - Dillon, Robin S.; Marsoobian, Armen T. (Wiley, 2018)
Criticism and Compassion: The Ethics and Politics of Claudia Card offers a unique perspective on the range of issues explored by Card during her distinguished career in philosophy. Investigates her work as an early leader in the development of feminist philosophy, challenging many preconceptions about the society’s norms regarding gender, marriage, and motherhood Crossing many disciplinary boundaries, her concept of social death has come to play a significant role in multidisciplinary field of genocide studies This volume combines many of Claudia Card’s important essays with recently commissioned essays by leading philosophers whose work has been influenced by Card The full scope of Card’s philosophy is presented here - both in her own words and those of her critics and interpreters
Keywords: dept.phi

Collective memory, memorialization and bearing witness in the aftermath of the Armenian Genocide - Marsoobian, Armen T. (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter describes and analyzes an ongoing project of memorialization of the Armenian Genocide in Turkey. It explores the importance of memorialization for collective historical memory, especially in situations where historical memory has been subverted by genocide denial. Among many aspects of memorialization, its role in bearing witness is explored and highlighted. Three components of the memory project are described: (1) the photography exhibitions, (2) the publications, and (3) the creation of memory sites. The project centers on the story of the Dildilian family in Ottoman Turkey before, during, and after the genocide, covering the years 1872–1923. A microhistory of the life of the Armenian minority is chronicled by means of the personal memories and stories of members of the family. The history is richly illustrated with photographs and drawings that serve as the basis of the photography exhibitions and books. Exhibitions and associated talks and panels have taken place in Istanbul, Merzifon, Diyarbakir, and Ankara. The chapter describes and analyzes the reaction of the Turkish public to the project.
Keywords: Armenian Genocide; Bearing witness; Collective memory; Genocide denial; Memorialization; Turkey; dept.phi

How do we memorialize genocide? The case of the German memorial to the murdered Jews of Europe - Marsoobian, Armen T (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This book explores the memory and representation of genocide as they affect individuals, communities and families, and artistic representations. It brings together a variety of disciplines from public health to philosophy, anthropology to architecture, offering readers interdisciplinary and international insights into one of the most important challenges in the 21st century. The book begins by describing the definitions and concepts of genocide from historical and philosophical perspectives. Next, it reviews memories of genocide in bodies and in societies as well as genocide in memory through lives, mental health and transgenerational effects. The book also examines the ways genocide has affected artistic works. From poetry to film, photography to theatre, it explores a range of artistic approaches to help demonstrate the heterogeneity of representations. This book provides a comprehensive and wide-ranging assessment of the many ways genocide has been remembered and represented. It presents an ideal foundation for understanding genocide and possibly preventing it from occurring again
Keywords: Aesthetics; Counter-monument; Health Psychology; Health psychology; History of World War II and the Holocaust; Holocaust; James E. Young; Jochen Gerz; John Dewey; Marian Marzynski; Memorial to the Murdered Jews of Europe; Memorial to the murdered jews of europe; Modernism; Noël Carroll; Peter Eisenman; Public Health; Public health; Public memorials; Sociology; Sociology, general; World War, 1939-1945; dept.phi

The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology, general; World War, 1939-1945; dept.phi

Value individualism and the popular-choice theory of secession - Cavallero, Eric (Social Theory and Practice, 2017)
Keywords: dept.phi